Development of a pressure-retaining separation and transfer system for sediment and overlying seawater - Guo, Jin; Zhou, Qixiao; Ge, Yongqiang; Li, Haonan; Gao, Qiaoling; Wang, Ying; Lin, Yuan; Chen, Jiawang (Frontiers in Marine Science, 2022)
Methane leakage at the interface between sediment and overlying seawater is an important basis for gas hydrate exploration. Therefore, a transfer device with working pressure of 30MPa and corresponding scheme are proposed to separate and transfer the sediment and overlying water inside the sampler under the condition of pressure-retaining. Based on the pressure relief valve with adjustable threshold pressure, the device transfers the overlying water by compressing the internal volume and transfers the sediment by secondary sampling. The performance of transfer device is studied by simulation and experiment. Based on the coupled Eulerian-Lagrangian approach in the Abaqus, the secondary sampling was investigated, and the penetration resistance and coring rate of the secondary sampling tube are 141N and 86.2%, respectively. By using the hydraulic simulation software AMESim, the pressure fluctuation caused by the movement of the mechanism during the transfer process was studied, and the pressure fluctuation amplitude is within 0.89 MPa. Furthermore, the laboratory transfer tests were carried out under high pressure conditions, and meantime, the simulation results are verified. Under the working condition of 30MPa, the device can maintain a pressure loss of no more than 8.0% (2.4MPa) within two hours, maintain pressure fluctuations during the transfer process within 4.8% (1.44MPa), and ensure that the pressure in the culture kettle decreases by 4.7% relative to the pressure in the sampler after the transfer, which shows the feasibility of the device application.